TINDAK TINDAK PRAGMATIK ANAK USIA PRASEKOLAH DWIBAHASAWAN JAWA-INDONESIA - Mukaromah Mukaromah (LITERA, 2008)
This study aims to investigate speech acts in Indonesian uttered by Indonesian-Javanese bilingual preschoolers. The study employed the qualitative approach.The theories employed were theories on pragmatics and language acquisition. Theresearch subjects were Indonesian-Javanese bilingual preschoolers. The researcherwas the key instrument. The data were collected through observations, field notes,and recording. The data were analyzed by using the discursive technique. The resultsof the study show forms of preschoolers’ pragmatic competence acquisition.The forms include pragmatic aspects in the utterances in the communication in accordancewith the context of use. The pragmatic aspects comprise deixis, presupposition,speech implicature, and conversation rules.Keywords: pragmatics, young learner, language acquisition